Long-term measurements of the erosion and accretion of dust deposits on comet 67P/Churyumov–Gerasimenko with the OSIRIS instrument. Issue 2 (9th April 2021) - Cambianica, P; Cremonese, G; Fulle, M; Simioni, E; Naletto, G; Pajola, M; Lucchetti, A; Penasa, L; Massironi, M; Frattin, E; Güttler, C; Sierks, H; et al.
ABSTRACT: We monitor the seasonal erosion and accretion of dust deposits in the Imhotep, Hatmehit, and Ma'at regions of comet 67P/Churyumov–Gerasimenko with OSIRIS Narrow Angle Camera images. The vertical accuracy of such measurements is 0.2 m and the spatial scale of the images we used is lower than 0.60 m pixel −1 . We calculate the height of 21 boulders by applying a tool that allows to measure the shadow length of a boulder projected on the surrounding dust deposit, assuming that any height variation is not due to boulder intrinsic change. Any boulder height variation provides a direct measurement about the thickness variation of the surrounding dust layer due to the occurring erosion and/or accretion. The analysis concerns the period from 2014 August, inbound to perihelion, to 2016 September, outbound. We measured the erosion in the Ma'at region of 0.6 ± 0.2 m from 2014 September 12 to December 2, and an erosion of 0.4 ± 0.3 m from 2014 December 3 to 2015 February 15. Then, we measured a dust deposition of 0.7 ± 0.3 m during the following perihelion phase, until 2016 May–September. This result confirms the link between the erosion of the Southern hemisphere and the fallout in the northern regions. The Imhotep and Hatmehit regions are characterized by a negligible erosion during the inbound orbit, consistent with pebble-made nucleus models predicting no erosion when the temperature of the nucleus surface is T s < 205 K.